2009
DOI: 10.1007/s11192-009-0065-3
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of world volatile organic compounds research trends

Abstract: This study explores a bibliometric approach to quantitatively assessing current research trends on volatile organic compounds, by using the related literature in the Science Citation Index (SCI) database from 1992 to 2007. The articles acquired from such literature were concentrated on the general analysis by scientific output, the research performances by countries, institutes, and collaborations, and the research trends by the frequency of author keywords, words in title, words in abstract, and keywords plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(72 citation statements)
references
References 35 publications
2
69
0
1
Order By: Relevance
“…[24,35] Distribution of title words, words in abstract, authors' keywords, and Key Words Plus over different periods of time have been thoroughly examined to elucidate research focus. [36,37] Key Words Plus in the Web of Science database supplied additional search terms extracted from the titles of articles cited by authors in their bibliographies and footnotes. [38] Word clusters has been further applied to determine the research foci and to characterize article lives in subsequent years.…”
Section: Abstract Analysismentioning
confidence: 99%
“…[24,35] Distribution of title words, words in abstract, authors' keywords, and Key Words Plus over different periods of time have been thoroughly examined to elucidate research focus. [36,37] Key Words Plus in the Web of Science database supplied additional search terms extracted from the titles of articles cited by authors in their bibliographies and footnotes. [38] Word clusters has been further applied to determine the research foci and to characterize article lives in subsequent years.…”
Section: Abstract Analysismentioning
confidence: 99%
“…Both ''carbon'' (2075; 7.9 %) and ''cell(s)'' (1846; 7.0 %) related to electrode(s) had an apparent upward progress in their ranks, from 21st and 40th in -1998to 4th and 5th in 2009 '', ''oxide'', ''treatment'', ''modified'', and ''nanotube(s)'' showed a continuous increasing trend in titles, while the terms ''solution(s)'' showed a decreasing trend. It is worth mentioning that ''Nanotube(s)'' had a notable promotion, the same with ''carbon nanotube(s)'' in author keywords, which did not appear in 1994-1998, but ranked 15th in 2009-2013. Distribution of words in article abstracts of different periods could also be the information of research trend analysis (Zhang et al 2010a;Fu et al 2014). In the analysis of article abstracts in current study, the words in article abstracts showed that ''electrochemical'', ''electrode(s) TP articles in the study period, R (%) the rank and percentage of the author keywords Appl Water Sci (2017) 7:13-30 23 ''process'', ''hydrogen'', ''acid'', ''oxygen'', ''cyclic'', ''properties'', ''aqueous'', and ''pH'' appeared at least 4,000 times.…”
Section: Articles Title and Articles Abstractmentioning
confidence: 99%
“…Science Citation Index Expanded TM , accessed via Web of Science TM Core Collection, was the most important and frequently used source database for an overview of scientific production. Bibliometric methods have been widely applied to assess the scientific outputs of various fields, especially on environmental concerns and energy utilization frontier, such as drinking water (Hu et al 2010), nitrate removal (Huang et al 2012), sediment (Niu et al 2014), solid waste (Fu et al 2010), volatile organic compounds (Zhang et al 2010a), and materials of lithiumbased batteries (Wagner et al 2013). In addition, research patterns including journals, categories, countries, and institutes, as well as the international cooperation had been broadly applied (Fu et al 2010Niu et al 2014;Tan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric methods concerning author keywords have only been used in recent years [20], and their use in analyzing research trends is rare [11,13,14,16]. In 1707 publications from 1992 to 2011, 599 (35.1 %) had author keywords.…”
Section: Distribution Of Author Abstract Analysismentioning
confidence: 99%
“…A common research tool for this analysis is the bibliometric method. The Science Citation Index Expanded (SCI-EXPANDED) from the Institute of Scientific Information (ISI) Web of Science databases is the most important and frequently used source for a broad review of scientific accomplishment in all fields [11,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%